House prices, household saving and financial market liberalization in Finland - Erkki Koskela; Heikki A. Loikkanen; Matti Virén (Bank of Finland, 1991)
This paper describes some institutional aspects of housing, markets and analyzes the price development of owner-occupied housing and its interaction with the household saving ratio in Finland during the last two decades. In Finland the volatility of house prices in relation to income can to a large extent be traced to the major changes in financial market conditions. Two other factors have also contributed to the house price volatility, namely the favourable tax treatment of housing (and othe.r) loans and the "thin" rental markets. The former has increased the rate of retum on housing, while the "thin" rental markets have resulted from rent regulation, which has decreased the supply of rental housing. The evidence suggests that in addition to the financial market conditions - measured by the households' indebtedness rate - both the after-tax rate of return and housing and the "thinness" of rental markets have all had a positive effect on house prices. Finally, demographic factors seym to have some, though relatively minor, role in house price development, while the real income variable cannot be estimated precisely. As for the linkages between housing markets and saving behaviour, our analysis lies in conformity with the view that the rate of change of real house prices has affected negatively and the after-tax nominal interest rate positively the household saving ratio. We are tempted to interpret these findings as suggesting that financial market conditions, and particularly.the financial market liberalization after the mid-1980 also explains the de cline in the household saving ratio during the housing market booms.
URN:NBN:fi:bof-201808011822
Keywords: 330